2008
DOI: 10.1002/ldr.842
|View full text |Cite
|
Sign up to set email alerts
|

Local perceptions and regional climate trends on the Central Plateau of Burkina Faso

Abstract: Due to devastating droughts in the 1970s and 1980s, climatic and environmental change in the West African Sahel has attracted a great deal of scientific research. While many of these studies documented a long-term trend of declining rainfall, analyses conducted in the last few years suggest that a 'recovery' is underway. Drawing on ethnographic interviews, focus groups, and participant observation in two Provinces of the Central Plateau of Burkina Faso, we elicited local perspectives on these rainfall trends f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 33 publications
10
132
0
5
Order By: Relevance
“…These regional rainfall trends and droughts are well-represented in the long-term rainfall record for Ouagadougou (Figure 4). This is also true for the shorter meteorological record available for Kongoussi and other stations (West et al 2008). There has been some recent improvement in precipitation and there is great scientific interest regarding Sahelian rainfall recovery and the "greening" of the Sahel (Herrmann et al 2005;Barbier et al 2009).…”
Section: Regional Desiccationmentioning
confidence: 95%
See 1 more Smart Citation
“…These regional rainfall trends and droughts are well-represented in the long-term rainfall record for Ouagadougou (Figure 4). This is also true for the shorter meteorological record available for Kongoussi and other stations (West et al 2008). There has been some recent improvement in precipitation and there is great scientific interest regarding Sahelian rainfall recovery and the "greening" of the Sahel (Herrmann et al 2005;Barbier et al 2009).…”
Section: Regional Desiccationmentioning
confidence: 95%
“…They also demonstrated that appropriate technologies based on local knowledge using locally available materials could help farmers adapt to decreased rainfall associated with Sahelian desiccation (West et al 2008). Overall, over 100,000 ha in the region have been rehabilitated with contour stone bunds since the mid-1980s (Reij et al 2005: 649).…”
Section: Soil and Water Conservation (Swc) Projectsmentioning
confidence: 99%
“…Therefore, knowledge of local communities on recent climate variability (\20 years) and adaptation measures is very valuable, particularly in the absence of reliable local observations and projections. Several studies such as (West et al 2008;Mertz et al 2009;Kemausuor et al 2011;Fosu-Mensah et al 2012;Tambo and Abdoulaye 2012) have already displayed high consistencies between local perceptions and observations. The IPCC Summary for Policymakers (2014) also showcased that ''adaptation planning and implementation at all levels of governance are contingent on societal values, objectives and risk perceptions.''…”
Section: Introductionmentioning
confidence: 93%
“…The issue has been frequently debated using qualitative information Adams 2001, Nielsen andReenberg 2010a,b) and relatively small samples or localized field sites (Tschakert 2007, Mbow et al 2008, West et al 2008, Barbier et al 2009, Mertz et al 2009b). The general conclusions have often been that it is too complex and difficult to isolate the climate factor from other driving forces of change because decisions taken are often influenced by many nonclimatic conditions, some of which often appear to be more important than the climate factors (Eakin 2005, Ziervogel et al 2006, Reid and Vogel 2006, Tschakert 2007, Mbow et al 2008.…”
Section: Introductionmentioning
confidence: 99%